Latinx writing Los Angeles : nonfiction dispatches from a decolonial rebellion - López-Calvo, Ignacio; Valle, Victor M. (Lincoln : University of Nebraska Press, 2018)
Latinx Writing Los Angeles offers a critical anthology of Los Angeles's most significant English-language and Spanish-language (in translation) nonfiction writing from the city's inception to the present. Contemporary Latinx authors, including three Pulitzer Prize winners and writers such as Harry Gamboa Jr., Guillermo Gómez-Peña, and Rubén Martínez, focus on the ways in which Latinx Los Angeles's nonfiction narratives record the progressive racialization and subalternization of Latinxs in the southwestern United States. While notions of racial memory, coloniality, biopolitics, internal colonialism, cultural assimilation, Mexican or pan-Latinx cultural nationalism, and transnationalism permeate this anthology, contributors advocate the idea of a contested modernity that refuses to accept mainstream cultural impositions, proposing instead alternative ways of knowing and understanding. Featuring a wide variety of voices as well as a diversity of subgenres, this collection is the first to illuminate divergent, hybrid Latinx histories and cultures. Redefining Los Angeles's literary history and providing a new model for English, Spanish, and Latinx studies, Latinx Writing Los Angeles is an essential contribution to southwestern and borderland studies.
LA's Latina/o phantom nonfiction and the technologies of literary secrecy / Victor Valle -- Decolonizing Latina/o nonfiction in LA's writing / Ignacio López-Calvo and Victor Valle -- "With the amicable people of Ensenada de Palmas": excerpt from Breve relación de la nueva entrada al sur, en la copiosa gentilidad de la nación de los coras ..., por el padre / Ignacio María Napoli, S.J. -- The public outcry. Noteworthy pamphlet / Francisco P. Ramírez -- The repercussions of a lynching / Ricardo Flores Magón -- To womankind, a manifesto / Blanca de Moncaleano -- Exerpt from "The Memoirs of Alfredo Cobos" / Alfredo Cobos -- Exerpts from The Journals of Anaïs Nin -- Bert Corona's "Struggle Is The Ultimate Teacher" / Jesús Mena --Beach blanket baja / Helena María Viramontes -- "The 'good old mission days' never existed: excerpt from The Medicine of Memory: A Mexican Clan in California / Alejandro Murguía -- Light at the end of tunnel vision: in memory of Gerardo Velázquez and Ray Navarro / Harry Gamboa Jr. -- "Deported to the north": excerpt from Dangerous Border Crossings: The Artist Talks Back / Gullermo Gómez-Peña -- Lights / Nylsa Martínez -- Movie version: "Hell to eternity" / Sesshu Foster -- Americanismo: city of peasants, Los Angeles, California / Héctor Tobar -- "The boy left behind": excerpt from Enrique's Journey / Sonia Nazario -- My father's house / Rubén Martínez.
Includes bibliographical references.
Print version record.
JSTOR
Keywords: American literature -- Hispanic American authors; American literature -- California -- Los Angeles; Hispanic Americans -- Literary collections; Hispanic Americans -- Intellectual life; Littérature américaine -- Auteurs américains d'origine latino-américaine.; Littérature américaine -- Californie -- Los Angeles; Américains d'origine latino-américaine -- Anthologies; Américains d'origine latino-américaine -- Vie intellectuelle; LITERARY CRITICISM -- American -- General; SOCIAL SCIENCE -- Ethnic Studies -- Hispanic American Studies; American literature; American literature -- Hispanic American authors; Hispanic Americans; Hispanic Americans -- Intellectual life; California -- Los Angeles; Literary collections